2014
DOI: 10.1039/c4tb01126k
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic coating of elastomer on different substrates using a liquid template to construct a biocompatible and antibacterial surface

Abstract: Elastomers were cast with a liquid template to create superhydrophobic, biocompatible, antifouling and antibacterial surfaces on virtually any substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Therefore, using biomaterial surfaces that resist bacteria attachment is an intuitive solution to this problem. 54 Super-hydrophobic polymer surfaces, such as very smooth silicone, polyurethane, polytetrafluoroethylene (PTFE), poly(vinyl chloride) (PVC), and polyethylene (PE), that have water contact angles larger than 150°, low surface energy, 55,56 as well as unique water repellent 57 and self-cleaning abilities, 56 are known to have resistance to microbial cell adhesion during short-term applications. 58 Hydrophilic surface modifications, such as the PEG modified surfaces discussed above, have also been widely characterized in the literature and have demonstrated excellent anti-adhesive properties for bacteria cells and proteins.…”
Section: Current Strategies For Creating Antibacterial Surfacesmentioning
confidence: 99%
“…Therefore, using biomaterial surfaces that resist bacteria attachment is an intuitive solution to this problem. 54 Super-hydrophobic polymer surfaces, such as very smooth silicone, polyurethane, polytetrafluoroethylene (PTFE), poly(vinyl chloride) (PVC), and polyethylene (PE), that have water contact angles larger than 150°, low surface energy, 55,56 as well as unique water repellent 57 and self-cleaning abilities, 56 are known to have resistance to microbial cell adhesion during short-term applications. 58 Hydrophilic surface modifications, such as the PEG modified surfaces discussed above, have also been widely characterized in the literature and have demonstrated excellent anti-adhesive properties for bacteria cells and proteins.…”
Section: Current Strategies For Creating Antibacterial Surfacesmentioning
confidence: 99%
“…4b in the tabulated form can be found in the ESI. 37 To account for the difference in hemolysis rates between regular and near-superhydrophobic surfaces, the mechanical force acting on the blood ow, which is a well-known source of hemolysis, 7,8,11 was examined. It had also been shown previously 36 that DH is proportional to t 0.785 , and it can be observed that the data points t closely to this trend, indicated as dashed lines (near-superhydrophobic surface) and solid lines (PVC surface) in Fig.…”
Section: Hemolysismentioning
confidence: 99%
“…The blood clotting time indexes (BCIs) on these surfaces had increased up to four times as compared to the corresponding BCIs on the pristine SEBS elastomer. They also showed good biocompatibility, the hemolysis ratio on the SEBS superhydrophobic coatings being up to eight-fold lower than that on the surface of the commercial SEBS elastomer [146].…”
Section: Biomimetic Hierarchical Micro-and Nanostructured Superhydropmentioning
confidence: 99%
“…Ye et al [146] developed a new bottom-up approach to the fabrication of superhydrophobic surfaces by casting a solution of an elastomer, styrene-b-(ethylene-co-butylene)-b-styrene (SEBS), on different substrates (glass, polymer, metal) followed by evaporation of the solvent. Unlike most polymers used to fabricate superhydrophobic surfaces by casting methods, which are crystalline or plastic at room temperature, elastomers are amorphous and soft, comparatively presenting a much looser packing and consequently increased mobility of the polymer chains.…”
Section: Biomimetic Hierarchical Micro-and Nanostructured Superhydropmentioning
confidence: 99%